ChemInform Abstract: Synthesis of a Novel UDP‐Carbasugar as UDP‐Galactopyranose Mutase Inhibitor. Issue 45 (23rd October 2014) - El Bkassiny, Sandy; N'Go, Ines; Sevrain, Charlotte M.; Tikad, Abdellatif; Vincent, Stephane P.
Abstract The synthesis of the novel UDP‐carbasugar (IV) involves the construction of the cyclohexene ring by a ring‐closing metathesis as the key step.